Features of Porous Anodic Alumina Growth in Galvanostatic Regime in Selenic Acid Based Electrolyte. (20th March 2017) - Nazarkina, Y.; Kamnev, K.; Dronov, A.; Dudin, A.; Pavlov, A.; Gavrilov, S.
Abstract: The features of porous anodic Al2 O3 formation process in galvanostatic regime in selenic acid based electrolyte under a range of anodization conditions were investigated. The growth process kinetics of porous anodic Al2 O3 was characterized by chronopotentiometric curves. The effect of electrolyte concentration, current density and anodization duration on the oxide porous structure ordering was studied by scanning electron microscopy. Approximate regions of self-ordered porous Al2 O3 formation process conditions were estimated. It was found that anodization parameters, at which self-ordered porous structure formation is observed, correspond to the conditions of equilibrium of oxidation and etching rates. It is shown that deviations from these conditions lead to the disordering of the porous structure.